Cryptocurrency Meets IoT: Unlocking New Business Horizons with Machine Learning - Celestin, Mbonigaba (RIRAI Publisher, 2025)
This research investigates the integration of cryptocurrency, the Internet of Things (IoT), and machine learning to explore innovative business opportunities. Using a mixed-methods approach, secondary data were analyzed, complemented by interviews and case studies, to evaluate the operational and financial impacts of these technologies. The study found a significant rise in cryptocurrency adoption in IoT systems, increasing from 12% in 2020 to 50% in 2024, driven by the scalability and security of blockchain. Machine learning contributed to a 25% reduction in operational inefficiencies and improved predictive maintenance. Additionally, businesses leveraging these technologies saw annual revenue growth of 20% and operational cost savings of up to 25% by 2024. However, challenges such as regulatory barriers, environmental concerns, and regional adoption gaps remain. The study concludes that fostering clear regulatory frameworks, enhancing infrastructure, and adopting green energy solutions are pivotal for maximizing the potential of these integrations. Key recommendations include investing in advanced IoT and blockchain platforms and promoting global adoption initiatives.